ANALISIS PENENTUAN HARGA POKOK PRODUKSI RECYCLE PET FLAKES DENGAN METODE FULL COSTING (Studi KASUS PT ABADI SINAR BARU INDAH) - Arizqi Kurnia Septin; Kafidin Muzakki; Devika Cherly Putrihadiningrum (Universitas Nahdlatul Ulama Sidoarjo, 2022)
This research is motivated by the increasing number of plastic waste scattered on this earth. The world's oceans are also increasingly polluted with plastic waste carried out by some people on this earth. Not far from happening in Indonesia. Indonesia is the second largest contributor to plastic waste in the world. How not, almost all Indonesian people daily encounter plastic to support their daily routines such as consuming food and drinks wrapped in plastic, shopping, and so on. Therefore PT. Abadi Sinar Baru Indah utilizes plastic waste which aims to reduce the spread of waste among the community by recycling plastic waste that has high economic value. PT. Abadi Sinar Baru Indah recycles PET (Polyethylene Terephthalate) plastic waste which is made from all kinds of beverage bottles. The purpose of this study is the method of determining the cost of production by applying the full costing method in the selling price at PT. Eternal New Beautiful Light. The research approach used is descriptive quantitative, with the results showing that the full costing method in the cost of production can determine the selling price at PT. Eternal New Beautiful Light. Because the full costing method will charge all BOP (Production Overhead Costs) both fixed and variable. Thus, the full costing method is more profitable for the company because it will charge all production operational costs in making a product. This will result in a more accurate cost of goods manufactured.